Enhancement of Suboptimal CD8 Cytotoxic T Cell Effector Function In Vivo Using Antigen-Specific CD80 Defective T Cells - Puliaeva, Irina (2010)
T cell upregulation of B7 molecules CD80 and CD86 limits T cell expansion in immunodeficient hosts; however, the relative roles of CD80 separate from CD86 on CD4 versus CD8 T cells in a normal immune system are not clear. To address this question, we used the parent-into-F1 (P→F1) murine model of graft-versus-host disease and transferred optimal and suboptimal doses of CD80 and/or CD86 knockout (KO) T cells into normal F1 hosts. Enhanced elimination of host B cells by KO T cells was observed only at suboptimal donor cell doses and was greatest for CD80 KO→F1 mice. Wild-type donor cells exhibited peak CD80 upregulation at day 10; CD80 KO donor cells exhibited greater peak (day 10) donor T cell proliferation and CD8 T cell effector CTL numbers versus wild-type→F1 mice. Fas or programmed cell death-1 upregulation was normal as was homeostatic contraction of CD80 KO donor cells from days 12–14. Mixing studies demonstrated that maximal host cell elimination was seen when both CD4 and CD8 T cells were CD80 deficient. These results indicate an important role for CD80 upregulation on Ag-activated CD4 and CD8 T cells in limiting expansion of CD8 CTL effectors as part of a normal immune response. Our results support further studies of therapeutic targeting of CD80 in conditions characterized by suboptimal CD8 effector responses.